Vertebrate road kill survey on a highway in southern Brazil - Corrêa, Luiz Liberato Costa; Silva, Darliane Evangelho; Oliveira, Stefan Vilges de; Finger, Júlia Victória Grohmann; Santos, César Rodrigo dos; Petry, Maria Virginia (Acta Scientiarum. Biological Sciences, 2017)
Highways are a major factor acting in the decline of several wildlife populations. Impact occurs due to the continuous flow of motor vehicles over tracks and collision with animals using the same area. This study aimed to list road killed wild vertebrates found in highways in the Pampa Biome, state of Rio Grande do Sul, over an entire year. The taxa found (amphibians, reptiles, birds and mammals) were identified to species level and their frequency of occurrence was seasonally registered. Along 2,160 km, we found 318 road killed individuals, totaling 65 species. This number represents an average of 0.147 road killed specimens by kilometer (that is, 1 individual each 7 km). Of these, seven species are under threat of extinction in the state of Rio Grande do Sul. We also found a seasonal pattern among road kills, in which the highest number of road killed animals was registered in the summer and spring months. These results contribute to increase knowledge about which species are most impacted by road kill on highways of the Pampa Biome. Such data can be used as an indicator for the implementation of measures by competent bodies to mitigate impacts of highways in the state of Rio Grande do Sul.